2016
DOI: 10.1037/emo0000104
|View full text |Cite
|
Sign up to set email alerts
|

The interpretative lenses of older adults are not rose-colored—just less dark: Aging and the interpretation of ambiguous scenarios.

Abstract: We are all faced with ambiguous situations daily that we must interpret to make sense of the world. In such situations, do you wear rose-colored glasses and fill in blanks with positives, or do you wear dark glasses and fill in blanks with negatives? In the current study, we presented 32 older and 32 younger adults with a series of ambiguous scenarios and had them continue the stories. Older adults continued the scenarios with less negativity than younger adults, as measured by negative and positive emotion wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Measures were collected across the entire task. The fEMG data were processed according to the protocol used in previous physiological examinations of affect (e.g., Mikels & Shuster, 2016). …”
Section: Methodsmentioning
confidence: 99%
“…Measures were collected across the entire task. The fEMG data were processed according to the protocol used in previous physiological examinations of affect (e.g., Mikels & Shuster, 2016). …”
Section: Methodsmentioning
confidence: 99%
“…As is often the case in studies of emotion, the negative emotion information may be stronger in nature relative to positive emotion information, and this may be particularly true when positive information is not present, as was the case in Experiment 1 but not in Experiment 2. Despite efforts to control for arousal, future work could extend these findings using pictures or other forms of emotional information, lists that contain both negatively and positively valenced words in addition to neutral words, and when people must interpret and recall ambiguous memories (cf., Mikels & Shuster, 2016). …”
Section: Methodsmentioning
confidence: 99%
“…At this point, the positivity effect has been widely documented: it has been observed in visual attention (Sasse, Gamer, Büchel, & Brassen, 2014), short-term memory (Mammarella, Di Domenico, Palumbo, & Fairfield, 2016), autobiographical memory (Kennedy, Mather, & Carstensen, 2004), and even working memory (Mikels, Larkin, Reuter-Lorenz, & Carstensen, 2005). The effect has been documented in attention to emotional faces (Fischer et al, 2005; Mather & Carstensen, 2003), memory for health information (English & Carstensen, 2015), and in the interpretation of socially ambiguous situations (Mikels & Shuster, 2016). A meta-analysis based on 100 studies concluded that the positivity effect was reliable and robust (Reed, Chan, & Mikels, 2014).…”
Section: Influence On My Research Programmementioning
confidence: 99%